Quality Test of Corn Flour from Pulut Corn Cob Waste ( Zea mays ceratina. L) by Fermentation - mirna, mirnawati (Jurnal Akta Kimia Indonesia (Indonesia Chimica Acta), 2023)
Pulut type corn or waxy corn has been developed in several areas in South Sulawesi. From year to year, the productivity of corn pulut has increased, this also shows that agricultural waste production has also increased. The agricultural waste produced by corn cobs. The purpose of this study was to determine the processing of corncob waste into cornflour and to determine the characterization of the quality of cornflour, especially microbial contamination based on SNI standards. Methods: water content using a gravimetric method, ash content using a gravimetric method, microbial contamination test using ALT method of 25-250 colonies/gram counted, and analysis of mold and E. coli bacteria. The results showed that the ash content was 0.0766%, 17.49 % moisture content, 17.49% protein content, ALT 1.9 x 106, mold analysis of 10,4 x 102 colonies/gram, and analysis of E. coli bacteria amounting to 8,1 APM / g and Bacillus cereus with a resistance value of <1.0 x 102coloni/g (negative value) indicates that it does not meet the SNI standard.